(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
An approach for computing the average moisture content of the whole quantity of wood materials in given batch subjected to steaming in an autoclave has been suggested. This value of the wood moisture content is needed for calculation and automatic realization of optimal energy saving regime for autoclave steaming of the materials. The approach is based on two own 2D mathematical models: one of the temperature distribution in non-frozen prismatic wood materials during their steaming and other – of the heat balance of the autoclave. The calculated by the models increase in the steaming medium temperature in the beginning of basic regime is compared with the real increase of that temperature, which is measured with a sensor in the automatic control system. After proper processing of the obtained differences between measured and calculated temperatures with the software package Table Curve, an equation for calculating the average moisture content of the wood materials in the batch loaded in an autoclave is derived. The application of the suggested approach for the cases of autoclave steaming of beech prisms in the production of veneer is presented.